Asymmetric warfare threats in Greece - Nomikos, John M. (Sodobni vojaški izzivi, 2020)
One of the biggest challenges of our time is the rise of asymmetric warfare threats. NATO and the EU are targeted by cybercrime syndicates, politically motivated non-state actors, and sophisticated state actors. Hostile cybercrime undermines all levels of society in NATO and the EU states, threatening political, economic, civil, and military security. Greece faces similar threats. This article focuses on the Greek cybersecurity strategy and analyses the causes and consequences of the terrorismorganized, illegal immigration nexus in Greece, and how essential it is to highlight the importance of collective intelligence sharing among the Greek security and intelligence community.
Keywords: asimetrično bojevanje; asymmetric warfare; cyber-security; Grčija; Greece; human trafficking; kibernetska varnost; migracije; migration; trgovina z ljudmi